2017
DOI: 10.1038/s41598-017-05617-1
|View full text |Cite
|
Sign up to set email alerts
|

Myosin 1b and F-actin are involved in the control of secretory granule biogenesis

Abstract: Hormone secretion relies on secretory granules which store hormones in endocrine cells and release them upon cell stimulation. The molecular events leading to hormone sorting and secretory granule formation at the level of the TGN are still elusive. Our proteomic analysis of purified whole secretory granules or secretory granule membranes uncovered their association with the actomyosin components myosin 1b, actin and the actin nucleation complex Arp2/3. We found that myosin 1b controls the formation of secreto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…Altogether, our data show that CgA binds to specific species of PA which in turn could act as lipid cofactors 55 at the TGN to induce membrane remodeling and curvature in order to initiate secretory granule budding, concomitantly or prior to the recruitment of cytosolic proteins such as GOLPH3, 54 arfaptins, 56,57 the actomyosin 1b complex, 58 or the membrane‐associated myristoylated protein HID1, 59 but also small GTPase of the Arf family, 60 all of which are also essential actors in this fundamental biological process necessary for regulated secretion. Further studies are now needed to evaluate the connection of CgA/PA interaction with the additional machinery involved in secretory granule biogenesis, in living neuroendocrine cells, and the potential implication of this interaction in diseases related to hormone secretion deregulation.…”
Section: Discussionmentioning
confidence: 76%
“…Altogether, our data show that CgA binds to specific species of PA which in turn could act as lipid cofactors 55 at the TGN to induce membrane remodeling and curvature in order to initiate secretory granule budding, concomitantly or prior to the recruitment of cytosolic proteins such as GOLPH3, 54 arfaptins, 56,57 the actomyosin 1b complex, 58 or the membrane‐associated myristoylated protein HID1, 59 but also small GTPase of the Arf family, 60 all of which are also essential actors in this fundamental biological process necessary for regulated secretion. Further studies are now needed to evaluate the connection of CgA/PA interaction with the additional machinery involved in secretory granule biogenesis, in living neuroendocrine cells, and the potential implication of this interaction in diseases related to hormone secretion deregulation.…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, in a previous study, we demonstrated that CgA expression induces the recruitment of cytoskeleton‐, GTP‐, and Ca 2+ ‐binding proteins at the level of the TGN in order to generate vesicles endowed with typical dynamics and exocytotic properties of neuroendocrine secretory granules in COS7 cells . More recently, we demonstrated that CgA induces the recruitment of the actomyosin 1b complex at the TGN membrane to control SG formation and the associated RSP in neuroendocrine and CgA‐expressing COS7 cells . Of note, early studies have reported that AP1‐clathrin attachment at the TGN membrane is essential for secretory granule budding although this notion has been debated by others .…”
Section: Chromogranin a Interacts With The Tgn Membrane To Direct Hormentioning
confidence: 70%
“…75 More recently, we demonstrated that CgA induces the recruitment of the actomyosin 1b complex at the TGN membrane to control SG formation and the associated RSP in neuroendocrine and CgA-expressing COS7 cells. 76 Of note, early studies have reported that AP1-clathrin attachment at the TGN membrane is essential for secretory granule budding although this notion has been debated by others. [77][78][79] Other studies demonstrated that the cytosolic protein, the BAR (Bin/Amphiphysin/ Rvs) domain protein Arfaptin-1, is recruited at PI(4)Penriched microdomains of the TGN membrane and allows the sorting of CgA to the RSP in human BON carcinoid tumor cells, 80 and that PKD-mediated Arfaptin-1 phosphorylation is necessary to ensure SG biogenesis in pancreatic β cells.…”
Section: Chromogranin a Interacts With The Tgn Membrane To Direct Hmentioning
confidence: 99%
“…Another group of proteins found upregulated in Tg197/Tg5519 ankles are involved in intracellular vesicular transport, endocytosis and invasiveness in extracellular matrix. MYO1B (Myosin IB) along with actin have been implicated in the control of secretory granule biogenesis and invagination of the plasma membrane during endocytosis (76). ACAP2 (ArfGAP With Coiled-Coil, Ankyrin Repeat And PH Domains 2), is a GTPase-activating protein that plays central role in endocytosis and FcγR-mediated phagocytosis (77), while CRP2 (Cysteine Rich Protein 2) is a new cytoskeletal component of invadopodia promoting breast cancer cell invasiveness and metastasis (78).…”
Section: Discussionmentioning
confidence: 99%